Green Human Resource Practices, Work–Life Balance, and Job Satisfaction: Employee Engagement as a Mediating Mechanism among Generation Z Employees - Balqis, Galuh Aura; Tutuko, Bambang; Cahyono, Hadi (Amkop Management Accounting Review (AMAR), 2026)
The growing presence of Generation Z in the workforce has prompted organizations to reconsider their human resource management approaches by placing greater emphasis on sustainability and employee well-being. Generation Z employees tend to prioritize mental health, work–life balance, and environmental values, which highlights the importance of implementing Green Human Resource Management (GHRM) and Green Work-Life Balance (GWLB) practices within organizations. This study seeks to examine the influence of GHRM and GWLB on Job Satisfaction, with Employee Engagement serving as a mediating variable among Generation Z employees at PT Petrokopindo Cipta Selaras.A quantitative research design was employed using a survey method. Data were collected through questionnaires distributed to Generation Z employees at PT Petrokopindo Cipta Selaras and analyzed using regression analysis and mediation testing techniques. The findings demonstrate that both GHRM and GWLB have a positive and significant impact on Employee Engagement. In addition, Employee Engagement was found to have a positive and significant effect on Job Satisfaction. The results further indicate that Employee Engagement plays a mediating role in the relationship between GHRM and GWLB and Job Satisfaction.Overall, the study suggests that the adoption of environmentally sustainable human resource practices and green-oriented work–life balance policies can foster higher levels of Employee Engagement, which in turn enhances Job Satisfaction among Generation Z employees. This research is expected to contribute to the literature on sustainable human resource management and offer practical insights for organizations in developing human resource policies that are aligned with the values and expectations of Generation Z.